Effects of feed enzymes and botanical blends in nursery pig diets on growth performance, bone characteristics, nutrient digestibility and intestinal morphology - Kim, Ty (Kansas State University, 2024)
This thesis contains three chapters that includes: 1) developing a phytase release curve to quantify the release of phytate-bound phosphorous in swine diets, 2) determining the effect of a botanical-derived feed additive containing extracts of capsicum oleoresin, clove essential oil, and garlic extract in diets with or without pharmacological levels of Zn and Cu, and 3) determining the effect of compound enzymes in reduced energy and protein diets. Chapter 1 utilized 280 nursery pigs to determine the effect of increasing phytase on nursery pig growth performance, bone characteristics, and plasma inositol concentrations. Increasing phytase from 250 to 2,000 FTU/kg in phosphorus deficient diets improved nursery pig growth performance, bone characteristics, and plasma inositol concentrations. Using formulated phytase concentrations, equations were developed for growth performance, bone ash weight, percentage bone ash, and bone density to predict aP release up to 2,000 FTU/kg of Sunphase HT phytase for 10- to 22- kg pigs. Chapter 2 involved 340 pigs to determine the effect of a botanical-derived feed additive containing capsicum oleoresin, clove essential oil, and garlic extract (CCG) on growth performance and fecal dry matter in nursery pig diets with or without pharmacological levels of Zn and Cu. Feeding pharmacological levels of Zn and Cu resulted in increased ADG and ADFI but lower fecal DM on d 21. Feeding CCG numerically increased ADG and ADFI in pigs not fed pharmacological levels of Zn and Cu and numerically decreased ADG and ADFI in pigs fed pharmacological levels of Zn and Cu. Chapter 3 utilized 355 pigs to determine the effects of compound enzymes, consisting of carbohydrases and protease, on growth performance, gut health, and nutrient digestibility in reduced energy and protein nursery pig diets. Pigs fed high energy diets had improved growth performance, ATTD of DM, CP, and ADF, and AID of Arg, Asp, and Trp compared to pigs fed low energy diets. Enzyme inclusion had no impact on overall growth performance but had a negative impact on duodenal morphology, ATTD of DM and CP, and AID of Met in low energy diets. In summary, these experiments provide data on aP release of Sunphase HT phytase, effect of a botanical-derived feed additive in nursery pig diets, and effect of compound enzymes in reduced energy and protein diets.
Keywords: Bone ash; Botanicals; Digestibility; Enzymes; Growth; Nursery pigs